Relationships among genome size, environmental conditions and geographical distribution in natural populations of NW Patagonian species of Berberis L. (Berberidaceae) - Bottini, M. C. J. (2000)
Variation in genome size of 24 populations belonging to 11 NW Patagonian species of Berberis was analysed as a function of the environment and geographical location. The variation showed three levels of discontinuity, two of which corresponded to diploid species (2n = 28) while the third corresponded to polyploid species (2n = 56). Diploids with DNA content ranging from 1.463 pg to 1.857 pg included Berberis cabrerae, B. chillanensis, B. montana, B. serrato-dentata and B. bidentata. Diploids with DNA content ranging from 2.875 pg to 3.806 pg included B. linearifolia, B. darwinii, B. parodii and B. empetrifolia. The genome size of the polyploid species B. buxifolia and B. heterophylla ranged from 5.809 pg to 6.844 pg. Principal component analysis (PCA) was applied to represent the variability of environmental conditions. The eigenvectors of the principal component axes showed that PCl discriminates the populations according to rainfall, types of vegetation and geomorphology; altitude and latitude, on the other hand, contribute to PC2 and PC3, respectively. From these results it is concluded: (1) that diploids with lower DNA content grow in high-elevation sites having greater rainfall but lower water availability; (2) diploids with higher DNA content are associated with half-elevation forests where the vegetative period is longer, the water availability is greater and the temperatures are higher; and (3) the distribution pattern of polyploids is considerably wider than that of diploids, which are geographically and ecologically restricted to forest areas. These results suggest that the C-value plays an important role in the ability of the species to adapt to different growing conditions.